N’dama Cattle Conservation: The Potential Roles of Artificial Insemination and the National Policy - Olaniyan, Olawale Festus; Hiemstra, Sipke-Joost (Richtmann Publishing, 2012)
Regular access to genetically superior bulls from an open nucleus breeding system is an impetus forN’Dama cattle utilization and conservation. However, shortage in the number of bulls that could bedistributed to the farmers for subsequent breeding remains a challenge in some countries of West Africa. Inthis regard, the potential benefit of artificial insemination (AI) and the roles of national policy was assessed.The open nucleus breeding scheme of International Trypanotolerance Center (ITC) in the Gambia was usedas a case study and the research questions were answered with literature review, focus group discussion,and Likert-scale questionnaire. Introduction of AI into the breeding scheme of N’Dama cattle can createhigher selection intensity and promote a wider dissemination of genetic gain made at the nucleus. Withimproved AI techniques, a better use of improved N’Dama bulls can be achieved. Notwithstanding, thereare concerns about low pregnancy rate, quality of the semen, inadequate knowledge of AI technicians, andthe regular availability of quality bulls. For the Gambian national policy, the environmental component isthe most relevant for conservation of N’Dama cattle. This can be buttressed with more flexibility and aclearer communication of the objectives through workshops and local media.